SILVER MAN'S ACTION IN PEKANBARU CITY - Nursyakdiah Nursyakdiah; Achmad Hidir (LPPM Institut Pendidikan Nusantara Global, 2022)
Silver Man is a social phenomenon which is currently being used as a job by some individuals who do not have a job. The purpose of this study was to find out: 1) The rationality of the actions of silver people in Pekanbaru City. 2) The joys and sorrows experienced by the silver man. This study applies a qualitative research method. The theory used is Talcott Parsons Action theory. The number of informants in this study were 4 people. The informant is a silver man. The results of this study are the rationality of the actions shown by the silver man on the main road, the purpose of which is to earn money and fulfill basic needs. Next are the joys and sorrows experienced by silver humans when they act on the streets. The likes that are generally felt are benefactors who give large amounts of money. The sorrows experienced by silver people varied, ranging from being kicked out during an action to never getting any income at all within one day of acting as a silver person.